The apothecary diaries. 6 - Hyūga, Natsu; Steinbach, Kevin (The apothecary diaries (Light novel), 2025)
"Despite Jinshi's feelings, Maomao still knows her place. She departs Gyokuyou's hometown with uncertainty for the future, but a detour during the return to the capital gives her unexpected insight into her own family. Meanwhile, an ugly scandal ensnares Consort Lishu. Could revealing the truth also unravel the mysteries of recent affairs?"--